Relationship between Nursing Students' Achievement Motivation and Self-efficacy of Clinical Performance - E Mohamadi; H Bana Derakshan; F Borhani; MJ Hoseinabadi Farahani; MA Pour Hoseingholi; N Naderi Ravesh (Iran University of Medical Sciences, 2014)
Abstract   Background & Aim: The Achievement Motivation is the cause of successful behavior and efforts in students. This study aims to determine the relationship between achievement motivation and self-efficacy of clinical performance in nursing students.   Material & Methods: This descriptive-Correlational study was conducted on 115 internship nursing students of Shahid Beheshti University of Medical Sciences. The sample was recruited by census. Data was collected by Hermans' Achievement Motivation Questionnaire and self-efficacy in clinical performance scale and analyzed by descriptive, non-parametric tests and Spearman correlation coefficient using SPSS-PC (v. 16).   Results: There was a significant relationship between achievement motivation and self-efficacy in clinical performance (r=0.61, P<0.01). Also an increase inachievement motivation and self-efficacy in clinical performance were significantly associated with student work experience and its duration, and students' total grade average (P<0.01) Conclusion: Regarding the findings, adoption of suitable educational strategies in line with promotion of achievement motivation and clinical self-efficacy is of high importance .